UMA-BCI Speller: An easily configurable P300 speller tool for end users. (April 2019) - Velasco-Álvarez, Francisco; Sancha-Ros, Salvador; García-Garaluz, Esther; Fernández-Rodríguez, Álvaro; Medina-Juliá, M. Teresa; Ron-Angevin, Ricardo
Abstract: Background and Objective: Some neurodegenerative conditions can severely limit patients' capability to communicate because of the loss of muscular control. Brain-computer interfaces may help in the restoration of communication with these patients, bypassing the muscular activity, so that brain signals can be directly interpreted by a computer. There are many studies regarding brain-controlled spellers; however, these systems do not usually leap out of the lab because of technical and economic requirements. As a consequence, the potential end users do not benefit from these scientific advances in their daily life. The objective of this paper is to present a novel brain-controlled speller designed to be used by patients due to its versatility and ease of use. Methods: The brain-computer interface research group of the University of Málaga (UMA-BCI) has developed a speller application based on the well-known P300 potential which can be easily installed, configured and used. The application supports the common P300 paradigms: the Row-Column Paradigm and the Rapid Serial Visual Presentation Paradigm. The inner core of the application is implemented with a widely used and studied platform, BCI2000, which ensures its reliability and allows other researchers to apply modifications at will in order to test new features. Ten naïve volunteers carried out exercises using the application and completed usability tests for evaluation purposes. Results: New subjects using the application managed to set up and use the proposed speller in less than an hour. The positive results of the evaluation through the usability tests support this application's ease of use. Conclusions: A new brain-controlled spelling tool has been presented whose aim is to be used by severely paralyzed patients in their daily lives, as well as by researchers to test new spelling features.